Faster speciation of fig‐wasps than their host figs leads to decoupled speciation dynamics: Snapshots across the speciation continuum. Issue 17 (26th August 2019) - Souto‐Vilarós, Daniel; Machac, Antonin; Michalek, Jan; Darwell, Clive Terence; Sisol, Mentap; Kuyaiva, Thomas; Isua, Brus; Weiblen, George D.; Novotny, Vojtech; Segar, Simon T.
Abstract: Even though speciation involving multiple interacting partners, such as plants and their pollinators, has attracted much research, most studies focus on isolated phases of the process. This currently precludes an integrated understanding of the mechanisms leading to cospeciation. Here, we examine population genetic structure across six species‐pairs of figs and their pollinating wasps along an elevational gradient in New Guinea. Specifically, we test three hypotheses on the genetic structure within the examined species‐pairs and find that the hypothesized genetic structures represent different phases of a single continuum, from incipient cospeciation to the full formation of new species. Our results also illuminate the mechanisms governing cospeciation, namely that fig wasps tend to accumulate population genetic differences faster than their figs, which initially decouples the speciation dynamics between the two interacting partners and breaks down their one‐to‐one matching. This intermediate phase is followed by genetic divergence of both partners, which may eventually restore the one‐to‐one matching among the fully formed species. Together, these findings integrate current knowledge on the mechanisms operating during different phases of the cospeciation process. They also reveal that the increasingly reported breakdowns in one‐to‐one matching may be an inherent part of the cospeciation process. Mechanistic understanding of this process is needed to explain how the extraordinary diversity of species, especially in the tropics, has emerged. Knowing which breakdowns in species interactions are a natural phase of cospeciation and which may endanger further generation of diversity seems critical in a constantly changing world.